2016
DOI: 10.3390/ma9100797
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Types A and B Gelatin Methacryloyl for Bioink Applications

Abstract: Gelatin methacryloyl (GelMA) has been increasingly considered as an important bioink material due to its tailorable mechanical properties, good biocompatibility, and ability to be photopolymerized in situ as well as printability. GelMA can be classified into two types: type A GelMA (a product from acid treatment) and type B GelMA (a product from alkali treatment). In current literature, there is little research on the comparison of type A GelMA and type B GelMA in terms of synthesis, rheological properties, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
160
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(173 citation statements)
references
References 29 publications
13
160
0
Order By: Relevance
“…Our results are generally in accordance with results reported by Lee et al., who also compared the DM of G A and G B methacryloyls: Their highest feed ratio of 0.1 mL MAAnh per 1 g gelatin corresponded roughly to our twofold molar excess (GM2). Like us, they observed a nearly quantitative conversion of amino groups and no difference in the DM between G A and G B derivatives at this feed ratio of MAAnh.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are generally in accordance with results reported by Lee et al., who also compared the DM of G A and G B methacryloyls: Their highest feed ratio of 0.1 mL MAAnh per 1 g gelatin corresponded roughly to our twofold molar excess (GM2). Like us, they observed a nearly quantitative conversion of amino groups and no difference in the DM between G A and G B derivatives at this feed ratio of MAAnh.…”
Section: Resultssupporting
confidence: 93%
“…Nevertheless, other studies on GM derivatives from lower to similar DMs than in this study, found that the mechanical stiffness of GM hydrogels increased in direct correlation with the DM . In conclusion, we suggest that physical and chemical cross‐linking complement each other in gels that are capable of both such as GM2 and GM5, and that an optimum can be achieved in terms of elastic gel stiffness, which can be predicted to be in the range of GM2 or GelMa2.2 as introduced in ref.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…whereby an increase in shear rate is corelated with a decrease in shear viscosity (), in line with previous studies (49,52). When the shear rate is increased, gelatin chains disentangle since molecular interactions are attenuated, and the corresponding solution viscosity is reduced.…”
Section: Characterisation Of Wet-spinning Solutionssupporting
confidence: 89%
“…GelMA is a temperature-sensitive material, which is more viscous at lower temperatures than at higher temperatures because of the reversible physical crosslinking. [27] Thus, the rheology of the GelMA bioinks can be readily regulated by adjusting the temperature. To examine the effect of PEO on the rheological properties of the GelMA-PEO emulsion bioinks, we examined the viscosity of different formulations of the GelMA-PEO emulsion bioinks as a function of temperature (Figure 2f).…”
mentioning
confidence: 99%